Performance Evaluation of A Multi-Sensor System Using Fixed Point DSP For Water Leak Detection - Loutfi Benyettou (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
DSPs (Digital Processors Signal) are processors specifically designed for digital signals processing. The fixed-point DSPs are processors operating in integer arithmetic whose characteristics are often limited but not less powerful with respect to floating-point DSPs. In this article, it is a question of checking the performances provided by the fixed-point DSP, the TMS320C541. This one is used in a detection and remote locating system ensuring a control of water leaks on the pipes. The acoustic correlation technique used as means of detection of these leaks represents the key element of the suggested system. In fact the DSP which deals the acquisition and processing of the signals emanating from the leaks. The had aim consists in initially to confirm the choice of such a processor for such an application. A simulation study to evaluate its performances as regards of computational accuracy and computing speed is carried out. A floating-point DSP of last generation, more accurate and faster, taken as reference element, is used for this purpose.